Metformin Causes G1-Phase Arrest via Down-Regulation of MiR-221 and Enhances TRAIL Sensitivity through DR5 Up-Regulation in Pancreatic Cancer Cells - Tanaka, Ryoichi; Tomosugi, Mitsuhiro; Horinaka, Mano; Sowa, Yoshihiro; Sakai, Toshiyuki (PLOS ONE, 2015)
Although many chemotherapeutic strategies against cancer have been developed, pancreatic cancer is one of the most aggressive and intractable types of malignancies. Therefore, new strategies and anti-cancer agents are necessary to treat this disease. Metformin is a widely used drug for type-2 diabetes, and is also known as a promising candidate anti-cancer agent from recent studies in vitro and in vivo. However, the mechanisms of metformin’s anti-cancer effects have not been elucidated. We demonstrated that metformin suppressed the expression of miR-221, one of the most well-known oncogenic microRNAs, in human pancreatic cancer PANC-1 cells. Moreover, we showed that the down-regulation of miR-221 by metformin caused G1-phase arrest via the up-regulation of p27, one of the direct targets of miR-221. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is also a promising agent for cancer treatment. While recent studies showed that treatment with only TRAIL was not effective against pancreatic cancer cells, the present data showed that metformin sensitized p53-mutated pancreatic cancer cells to TRAIL. Metformin induced the expressions of death receptor 5 (DR5), a receptor for TRAIL, and Bim with a pro-apoptotic function in the downstream of TRAIL-DR5 pathway. We suggest that the up-regulation of these proteins may contribute to sensitization of TRAIL-induced apoptosis. The combination therapy of metformin and TRAIL could therefore be effective in the treatment of pancreatic cancer.